O sábio e a imagem: estudos sobre Plutarco e a arte - Plutarco (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2014)
This book is organized into two parts, the first one focused specifically on the Plutarchian Corpus as a source for the study of art and iconography (sculpture, painting, and numismatics), the second one on the Life of Alexanderand its reception in Western art (painting, tapestry and cinema). It brings together seven studies by Spanish and Portuguese researchers, along with an introductory text. Based on different perspectives of analysis and up-to-date bibliography, though focused in the work of Plutarch, this volume is also a contribution to research in the field of Classical Art and Reception Studies.